LOCAL GOVERNMENTS AND EDUCATION IN CHILE IN THE NINETEENTH CENTURY: A HISTORICAL APPROACH - Castro Paredes, Moyra (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2011)
Most discussions and analysis of Educational Municipalization (small towns) in Chile refer to a phenomenon rather contemporary. The article reconstructs from historical and educational events the municipal school system, colonial-home-based on the tasks of the chapters in the teaching of their territory in the early institutional life of the country. Because of this, we describe the most important educational expressions of indigenous communities, the aftermath of the Hispanic presence and the itinerary of the nineteenth century, linked to the organization in the country and the performance of subnational governments. The text ends with some reflections that contribute to the memory of education, not only to deepen paths and any restrictions, but to make his career-education and local governments, which gives coherence and significance to the local educational question-present.